Electrochemical Patterning of Cu Current Collectors: An Enabler for Pure Silicon Anodes in High‐Energy Lithium‐Ion Batteries. Issue 22 (1st July 2022) - Schlaier, Jonas; Cangaz, Sahin; Maletti, Sebastian; Heubner, Christian; Abendroth, Thomas; Schneider, Michael; Kaskel, Stefan; Michaelis, Alexander
Abstract: Silicon (Si) is considered the most promising anode material for next‐generation high‐energy lithium‐ion batteries. To enable the use of pure Si anodes, patterning is essential to reduce electrode degradation caused by volume changes during cycling. The authors herein report a facile and scalable Cu electrodeposition (Cu‐ECD) process to tailor the topography of Cu current collectors for the directed formation of columnar Si anodes by physical vapor deposition (PVD). ECD parameters, such as Cu concentration, temperature, potential, and deposited amount of Cu, are systematically varied. The most promising ECD parameters are applied to modify commercial Cu foils, which are then used to prepare columnar Si anodes via PVD. Modified current collectors and resulting Si anodes are investigated by scanning electron microscopy (SEM), laser scanning confocal microscopy, and adhesion tests. Selected Si anodes are characterized in battery cells regarding cycling stability. It is shown that the adjustment of the current collector topography results in a significant increase in cycling stability. SEM analysis revealed differences in the mechanical degradation and electrochemical capacity decay. Based on the results, process–structure–property relationships between the topography of the Cu‐ECD current collectors, the resulting columnar Si anodes and their electrochemical performance are derived. Abstract : The electrochemical patterning of current collectors represents a versatile and scalable strategy for improving the stability of battery electrodes. Different regimes of Cu deposition from an aqueous electrolytes are investigated, and promising deposition parameters are identified. Understanding the trade‐off between surface roughness and mechanical stability of deposits enables to fabricate current collectors for stable Si thin films.